2018
DOI: 10.29252/hmj.22.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pilates Exercise Training on Serum Osteocalcin and Parathormone levels in inactive and overweight women

Abstract: Introduction: Experimental evidence suggests positive effects of physical activity on skeletal mass. Biochemical markers determine the response rate of bone metabolism to physical activity. Therefore, the aim of this study was to investigate the effect of Pilates exercise training on serum osteocalcin and parathormone levels in inactive and overweight women. Methods: 28 healthy overweight women participated in this quasi-experimental study. They were randomly divided into two groups: exercise group (n=14) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Then we initially screened out 2,502 articles through title and abstract, and the remaining 60 were considered highly relevant. Finally, we further excluded 49 studies by means of reading full text according to our study selection criteria, leaving 11 studies (Cakmakçi, 2011 ; Gorji et al, 2014 , 2015 ; Chaudhary, 2016 ; Savkin and Aslan, 2016 ; Khormizi and Azarniveh, 2017 ; Khajehlandi et al, 2018 ; Chen J. et al, 2020 ; Jung et al, 2020 ; Tyagi and Kumar, 2020 ; Wong et al, 2020 ) for inclusion in this analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then we initially screened out 2,502 articles through title and abstract, and the remaining 60 were considered highly relevant. Finally, we further excluded 49 studies by means of reading full text according to our study selection criteria, leaving 11 studies (Cakmakçi, 2011 ; Gorji et al, 2014 , 2015 ; Chaudhary, 2016 ; Savkin and Aslan, 2016 ; Khormizi and Azarniveh, 2017 ; Khajehlandi et al, 2018 ; Chen J. et al, 2020 ; Jung et al, 2020 ; Tyagi and Kumar, 2020 ; Wong et al, 2020 ) for inclusion in this analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were RCTs involving 393 adults with overweight or obesity. The studies were from Korea (Jung et al, 2020 ), Turkey (Cakmakçi, 2011 ; Savkin and Aslan, 2016 ), Iran (Gorji et al, 2014 , 2015 ; Khormizi and Azarniveh, 2017 ; Khajehlandi et al, 2018 ), the USA (Wong et al, 2020 ), India (Chaudhary, 2016 ; Tyagi and Kumar, 2020 ), and China (Chen J. et al, 2020 ). These studies were published between 2011 and 2020, and the intervention duration varied from 8 to 24 weeks, with the sample size ranging from 20 to 61 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, such an alternative muscle-strengthening activity may provide an inclusive environment and exceptional improvements in functional task outcomes [ 49 ]. However, in the present review, only one study investigated flexibility [ 53 ] and maximal aerobic capacity [ 60 ] in this cohort, highlighting the gap in the literature concerning strong evidence related to the efficacy of Pilates training on physical and motor fitness parameters in individuals with overweightness and obesity. On the other hand, a few studies investigating the Pilates training method have shown that it can be an effective exercise mode for increasing functional capacity, flexibility, balance, posture, and muscular performance in various healthy and clinical populations [ 74 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 98%